Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1136/jcp.51.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Helicobacter pylori vacA genotype in Japanese patients with gastric cancer.

Abstract: Aim-To examine the vacA genotypes of Helicobacter pylori strains in Japan and to define whether any specific genotype was associated with gastric cancer. Methods-The allelic variation of vacA gene was studied using a recently introduced polymerase chain reaction based vacA genotyping system. Results-80 H pylori strains were isolated from gastric biopsies of 40 patients with gastric cancer and 40 control subjects in a Japanese population. All strains were s1/m1 subtype and 79 of 80 strains were classified as s1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 11 publications
(7 reference statements)
0
15
0
1
Order By: Relevance
“…There is global variation in the distribution of vacA alleles in different ethnic populations (27). The prevalence of s1c and s1a is high in strains from Asia; however, s1b is frequent in Southern Europe, South America, South Africa, and the United States (14,22,27,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is global variation in the distribution of vacA alleles in different ethnic populations (27). The prevalence of s1c and s1a is high in strains from Asia; however, s1b is frequent in Southern Europe, South America, South Africa, and the United States (14,22,27,29).…”
mentioning
confidence: 99%
“…However in Japan, South Korea, and China, where s1 alleles predominate, vacA genotypes have not been associated with more severe clinical outcome (20,22,29). Global variation in the distribution of vacA alleles may explain diverse reports linking vacA genotype to clinical disease from different geographic areas.…”
mentioning
confidence: 99%
“…The association of the speci®c vacA genotypes with cytotoxin activity Med Microbiol Immunol (1999) 188: 131±138 and peptic ulcers was ®rst described for H. pylori isolates from the United States [2,5] and con®rmed in several studies [17,23,27,30,34]. Of note, this association was not found in H. pylori strains from Japanese patients [19,21,29,39], or other countries [8,38]. One United States study also failed to demonstrate an association [15].…”
Section: Introductionmentioning
confidence: 91%
“…However, the number of H. pylori strains that remain untypeable is considerable [8,15,17,19,21,23,25,27,29,30,34,37,39]. The originally described primer set [2] requires separate PCR runs to type m1 and m2.…”
Section: Introductionmentioning
confidence: 99%
“…It may be concluded that the s1 allele is linked to peptic ulcer development, and hence to greater virulence. However, despite this association between s1/m1 vacA genotype and presence of peptic ulcer, together with an increased infiltration by neutrophils and lymphocytes in vivo, greater in ulcer patients versus gastritis patients, this association is not so obvious in Asian countries, where both conditions exhibit a similar incidence regarding the s1/m1 genotype (41,42).…”
Section: Vacuolizing Cytotoxin (Vaca)mentioning
confidence: 99%